2018
DOI: 10.1038/s41467-018-05778-1
|View full text |Cite
|
Sign up to set email alerts
|

Diet and the epigenome

Abstract: Over the past decade, remarkable breakthroughs in our understanding of epigenetic biology have coincided with an increased public interest in the impact of diet and lifestyle choices on health. It is well established that a balanced diet enhances life expectancy and helps to prevent or treat certain diseases, such as obesity, diabetes, cancer, and mental disorders. However, the biological mechanisms underlying these effects are not yet well understood. In this commentary, we highlight several recent studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 10 publications
2
119
0
Order By: Relevance
“…[10] Aided by synthetic and analytical advancements,ahuge range of potential host materials has now been reported (Figure 2), which encompasses metal oxides, [11][12][13][14] metal hydroxides, [15,16] metals (also termed single-atom alloys (SAAs)), [17,18] micro/ mesoporous materials such as zeolites, [19,20] metal-organic frameworks (MOFs), [21,22] silicas, [23,24] carbon-based materials, [25][26][27][28] organopolymers, [29,30] nitrides, [31][32][33] and carbides. [10] Aided by synthetic and analytical advancements,ahuge range of potential host materials has now been reported (Figure 2), which encompasses metal oxides, [11][12][13][14] metal hydroxides, [15,16] metals (also termed single-atom alloys (SAAs)), [17,18] micro/ mesoporous materials such as zeolites, [19,20] metal-organic frameworks (MOFs), [21,22] silicas, [23,24] carbon-based materials, [25][26][27]…”
Section: Properties Of Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Aided by synthetic and analytical advancements,ahuge range of potential host materials has now been reported (Figure 2), which encompasses metal oxides, [11][12][13][14] metal hydroxides, [15,16] metals (also termed single-atom alloys (SAAs)), [17,18] micro/ mesoporous materials such as zeolites, [19,20] metal-organic frameworks (MOFs), [21,22] silicas, [23,24] carbon-based materials, [25][26][27][28] organopolymers, [29,30] nitrides, [31][32][33] and carbides. [10] Aided by synthetic and analytical advancements,ahuge range of potential host materials has now been reported (Figure 2), which encompasses metal oxides, [11][12][13][14] metal hydroxides, [15,16] metals (also termed single-atom alloys (SAAs)), [17,18] micro/ mesoporous materials such as zeolites, [19,20] metal-organic frameworks (MOFs), [21,22] silicas, [23,24] carbon-based materials, [25][26][27]…”
Section: Properties Of Sacsmentioning
confidence: 99%
“…One of the first challenges in the development of SACs was how to stabilize metal atoms against sintering or leaching in sufficient amounts to give appreciable activity.M etalcontaining zeolites and zeotypes,inwhich metal centers were mainly isolated in crystallographic positions,were among the most notable early examples of successful SACs. [10] Aided by synthetic and analytical advancements,ahuge range of potential host materials has now been reported ( Figure 2), which encompasses metal oxides, [11][12][13][14] metal hydroxides, [15,16] metals (also termed single-atom alloys (SAAs)), [17,18] micro/ mesoporous materials such as zeolites, [19,20] metal-organic frameworks (MOFs), [21,22] silicas, [23,24] carbon-based materials, [25][26][27][28] organopolymers, [29,30] nitrides, [31][32][33] and carbides. [34] Further extending the diversity of this framework with host functionalization strategies (such as,t hrough partial surface hydration, [35] introduction of alkali metals, [36] or decoration with ethylene glycolate species [37] )h as also been demonstrated to successfully enhance the anchoring of metal atoms.…”
Section: Properties Of Sacsmentioning
confidence: 99%
“…Studies have shown that dietary components interact with our epigenome and could have long-lasting effects [70,71]. In this section, we will present the beneficial effects of the supplementation of choline during early development on brain cognitive functions later in life.…”
Section: Choline and Other Methyl Donors As Modulators Of Neuronal Plmentioning
confidence: 99%
“…Dietary components intake during early life could exert long-lasting effects on mental health [70] as the brain during early development is plastic and undergoes rapid growth and differentiation for its normal functioning. One carbon metabolism is influenced by nutritional status [72].…”
Section: Choline Other Methyl Donors and The Developing Brainmentioning
confidence: 99%
“…Various types of dysregulation at the RNA level can generate immunogenic peptides in cancer cells [13][14][15] . Notably, tumors harbor up to 30% more alternative splicing (AS) events than normal tissues, and the resulting peptides are predicted to be presented by human leukocyte antigen (HLA) 16 .…”
Section: Mainmentioning
confidence: 99%